Left cerebral cortex complexity differences in sporadic healthy individuals with auditory verbal hallucinations: A pilot study. (March 2020) - Zhuo, Chuanjun; Li, Gongying; Chen, Ce; Ji, Feng; Lin, Xiao; Jiang, Deguo; Tian, Hongjun; Wang, Lina; Lin, Xiaodong; Ping, Jing
Highlights: We examined structural brain alterations in healthy individuals with AVHs (Hi-AVHs). Hi-AVHs exhibited increases in the gyrification index in the left cerebral cortex. Hi-AVHs also exhibited increased fractal dimensions in the left cerebral cortex. Our results are in accordance with the integrated network model of hallucinations. AVHs may represent a vulnerability factor for schizophrenia in healthy individuals. Abstract: In the present pilot study, we aimed to characterize the brain surface differences between 42 sporadic healthy individuals with AVHs (Hi-AVHs) and 50 healthy individuals without AVHs. The Auditory Hallucinations Rating Scale (AHRS) was used to assess the severity of AVHs, while the gyrification index and fractal dimensions were used to evaluate cerebral cortex complexity. We observed a significant increase of the gyrification index was located in the left superior temporal gyrus, the left temporoparietal junction, the left superior frontal gyrus, and the left parietal lobe. The fractal dimensions had significantly increased in the left Wernicke's area, the left Broca's areas and the left parietal lobe. Our pilot findings indicated gyrification index and fractal dimensions differences were only located in the left hemisphere between the groups of Hi-with and without AVHs. However, these differences did not correlate with the AVHs symptoms, and the non-hallucinating healthy individuals did not demonstrate corresponding reverse changes; hence we cannot postulate that cerebral cortex complexity alterations are related to AVHs. Our pilot study provides a clue for further studies aimed at investigating the brain features of Hi-AVHs.